Instilling The Values of Nationalism in Historical Learning in Metro 1 State Senior High School Lampung - *Wa Ima; Muhammad Rijal Fadli; Jems Sopacua (Universitas Syiah Kuala, 2022)
The purpose of this research is (1) to describe the process of learning history that takes place in Metro 1 State Senior High School Lampung, and (2) Steps to instill the values of nationalism in history learning in students in Metro 1 State Senior High School Lampung. Descriptive qualitative method used in this study. Data analysis techniques using data triangulation taken from observation techniques, in-depth interviews, and documentation. The results showed that history learning in Metro 1 State Senior High School has been running effectively because schools have implemented a moving class system that is carried out in certain learning spaces according to their fields. While the inculcation of nationalism values is done through the integration of nationalism values in learning history, so teachers must play an active and innovative role in planning learning that is inserted in the Syllabus and RPP. As for the values of nationalism that are inculcated through culture and habituation of the school environment with attitudes such as discipline, tolerance, patriotism, responsibility, courtesy, hard work, and mutual cooperation and so forth.